School health services from a global perspective: models, systemic challenges, and policies - Dogan, Muhammet Fatih (BMC, 2026)
This meta-synthesis provides a comprehensive examination of the historical development, theoretical frameworks, and practical challenges associated with School Health Services (SHSs). Research indicates that SHSs have undergone a significant paradigm shift, moving from a reactive disease-management model to a proactive, salutogenic approach that holistically promotes health. Central to this modern system is the school nurse, whose role has expanded from providing clinical care to advocating for public health. However, the study demonstrates that a significant barrier constrains the potential of this ideal model, conceptualised here as systemic burden. Inadequate funding, chronic staff shortages, and mounting administrative responsibilities hinder school nurses' preventive work, confining them to a reactive role and creating a significant disparity between policy and practice. A comparative analysis of different national models substantiates that the efficacy of SHSs is directly correlated with the investment and resource allocation dedicated to the system. Consequently, an effective SHSs programme is not a luxury but a strategic investment in a nation's educational and health infrastructure. Its success depends on a system that is empowered, adequately staffed, and sustainably funded to enable school nurses to fulfil their role comprehensively.
Keywords: School health services; School nursing; Systemic burden; Public health; Meta-synthesis; PROGRAM; Public, Environmental & Occupational Health